2010
DOI: 10.1371/journal.pcbi.1001041
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Heterogeneity, Excitation and Conduction in the Sinoatrial Node: A Model Study

Abstract: The sinoatrial node (SAN) is a complex structure that exhibits anatomical and functional heterogeneity which may depend on: 1) The existence of distinct cell populations, 2) electrotonic influences of the surrounding atrium, 3) the presence of a high density of fibroblasts, and 4) atrial cells intermingled within the SAN. Our goal was to utilize a computer model to predict critical determinants and modulators of excitation and conduction in the SAN. We built a theoretical “non-uniform” model composed of distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 43 publications
5
65
0
Order By: Relevance
“…This study showed that both fibroblast density and heterocellular coupling conductance exhibit a biphasic effect on the frequency of spiral waves and that both impact the wave stability. Similar results were obtained in the sinoatrial node by Oren et al [100] and in ventricular tissue.…”
Section: Consequences Of Fibrosis Derived From Computational Studiessupporting
confidence: 88%
“…This study showed that both fibroblast density and heterocellular coupling conductance exhibit a biphasic effect on the frequency of spiral waves and that both impact the wave stability. Similar results were obtained in the sinoatrial node by Oren et al [100] and in ventricular tissue.…”
Section: Consequences Of Fibrosis Derived From Computational Studiessupporting
confidence: 88%
“…Previous SAN models to date have been 1D or a thin radial slice (8,30) and are, thus, unable to capture the phenomenon studied herein. Building upon histological, anatomical, and mapping studies, our SAN model captured a broad array of experimentally observed behavior and offers comprehensive mechanistic insight into SAN function and neurally induced AF genesis.…”
Section: Discussionmentioning
confidence: 97%
“…Recent SAN modeling studies have been limited to one dimension or a thin radial slice (8,30), and thus the inferior/superior LPS shifting has not been a target of study. Furthermore, extension of these one-dimensional (1D) gradient models to three-dimensional (3D) is ambiguous, as it can be performed by either rotation or translation.…”
mentioning
confidence: 99%
“…fibroblasts, neurons, etc. The interested reader is referred to the most recent achievements in the numerical modeling in this exciting area of research (137, 138), including pathological aspects of SA node function (139, 140). …”
Section: Summary and Future Directionsmentioning
confidence: 99%